Family Ownership, Independent Oversight, and Financial Information Transparency: Evidence From Asia - Siti Nuke Nurfatimah; Zuni Barokah (The Indonesian Journal of Accounting Research, 2017)
This study examines the association between family ownership and financial information transparency of large corporations in the Asian region and whether independent oversight (i.e., independent directors and external auditors) influences such relationship. The transparency of financial information is measured using earnings’ opacity which includes three dimensions, i.e., profit aggressiveness, loss avoidance, and income smoothing. The findings show a positive association between family ownership and financial information transparency. Further, we find that both independent director and external auditors negatively influence the relationship between family ownership and financial information transparency. Firms with a higher percentage of family ownership tend to have a weaker role of board independence, which leads to less transparent financial information. Lastly, external auditors also seem to have limited power in reducing earnings opacity in family firms.